Orange-collar labor: work and inequality in prison - Gibson-Light, Michael (Oxford University Press, 2023)
"In addition to holding nearly a quarter of the world's legal captives, the United States puts them to work. Close to two-thirds of those held in state prisons hold some sort of job within their institution. For them, prison is not only a place of punishment, but a workplace as well. Yet, very little is known about work behind bars. To illuminate the "black box" of modern prison labor, Michael Gibson-Light conducted 18 months of ethnographic observations and over 80 interviews with currently-incarcerated men as well as staff members within one of America's many medium-security prisons. This book pulls together these accounts to paint a picture of daily labors on the inside, showing that not all prison jobs are the same, nor are all imprisoned workers treated equally. While some find value and purpose in higher-paying, more desirable jobs, others struggle against monotony and hardship in lower-paying, deskilled worksites. The result is a stratified prison employment system in which race, ethnicity, nationality, and social class help determine one's position, which shapes their experiences of incarceration and often their ability to prepare for release. Through insightful first-hand perspectives and rich ethnographic detail, Orange-Collar Labor takes the reader inside the prison workplace, illustrating the formal prison economy and labor system alongside the informal black market on which many rely to survive. Highlighting moments of struggle and suffering, as well as hard work, cooperation, resistance, and dignity in harsh environments, it documents the lives of America's working prisoners and the inequalities they face"--